Three aspects of neural signalling with focus on pain – propagation, inhibition and application - Mona, Johansson (My University, 2011)
This thesis includes three different aspects of neural signalling, a new mathematical model for the action potential and its propagation, an experiment of how general anaesthetic affect the membrane of a neuron and speculations about what mechanisms underlie pain relief of the bioelectric dressing; ProcelleraTM . At present the mathematical models for an action potential and its propagation is based on Hodgkin & Huxley´s model which is heavily founded on experimental result and consists of a very complex expression. This thesis present a new model which is based on the observed phenomenon that the axon is expanded when the action potential is transferred, this results in a much simpler expression. These equations are also visualized through simulations in finite element method based programme, COMSOLTM and show the same behaviour as an action potential, i.e. a pulse shape. The essential feature of general anaesthetic is that it inhibits neural signals. How it does this is debated in the scientific community. Different field of science provides different explanations. There is a well known rule; the Meyer-Overton rule which says that the effect of general anaesthetic is proportional to its solubility in olive oil which resembles the axon membrane. This thesis presents experiments where QCM-D (Quartz Crystal Microbalance with Dissipation monitoring) is used to observe how the resonance frequency and dissipation of a membrane is change when general anaesthetic is dissolved in it. It also present an experiment monitoring the electrical properties changes of the membrane due to general anaesthetic. The bioelectric dressing ProcelleraTM is at present claimed to reduce the pain sensation in a wound, by inhibition of the pain signal. The dressing contains zinc and silver elements and therefore this thesis speculates in how these metals can result in pain reduction. This speculation discuss different receptors inhibition, chemical reactions and other mechanisms which are possible to occur in the interaction of the dressing and the wound.
Keywords: Den kondenserade materiens fysik; Condensed Matter Physics